Biomechanical evaluation and comparison of clinically relevant versus non-relevant leg length inequalities - Michalik, Roman; Rissel, Viola; Migliorini, Filippo; Siebers, Hannah Lena; Betsch, Marcel (BMC musculoskeletal disorders, 2022)
Leg length inequalities are a frequent condition in every population. It is common clinical practice to consider LLIs of 2 cm and more as relevant and to treat those. However, the amount of LLIs that need treatment is not clearly defined in literature and the effect of real LLIs on the musculoskeletal system above and below 2 cm have not been studied biomechanically before. By using surface topography, we evaluated 32 patients (10 females, 22 male) with real LLIs of ≥ 2 cm (mean: 2.72 cm; n = 10) and compared their pelvic position and spinal posture to patients with LLIs < 2 cm (mean: 1.24 cm; n = 22) while standing and walking. All patients were measured with a surface topography system during standing and while walking on a treadmill. To compare patient groups, we used Student t-tests for independent samples. Pelvic obliquity was significantly higher in patients with LLI ≥ 2 cm during the standing trial (p = 0.045) and during the midstance phase of the longer leg (p = 0.023) while walking. Further measurements did not reveal any significant differences (p = 0.06-0.706). The results of our study suggest that relevant LLIs of ≥ 2 cm mostly affect pelvic obliquity and do not lead to significant alterations in the spinal posture during a standing trial. Additionally, we demonstrated that LLIs are better compensated when walking, showing almost no significant differences in pelvic and spinal posture between patients with LLIs smaller and greater than 2 cm. This study shows that LLIs ≥ 2 cm can still be compensated; however, we do not know if the compensation mechanisms may lead to long-term clinical pathologies.
Gesehen am 14.05.2024